2014
DOI: 10.1038/cddis.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

Impact of human papilloma virus infection on the response of head and neck cancers to anti-epidermal growth factor receptor antibody therapy

Abstract: Infection with human papillomaviruses (HPVs) characterizes a distinct subset of head and neck squamous cell cancers (HNSCCs). HPV-positive HNSCC preferentially affect the oropharynx and tonsils. Localized HPV-positive HNSCCs have a favorable prognosis and treatment outcome. However, the impact of HPV in advanced or metastatic HNSCC remains to be defined. In particular, it is unclear whether HPV modulates the response to cetuximab, an antibody targeting the epidermal growth factor receptor (EGFR), which is a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…The relative contribution of EGFR expression and signaling to HPV[+] HNSCC development and progression (compared with HPV[−] HNSCC) is not well understood. HPV oncogenes have not been shown to modulate the anti-EGFR antibody responses in HNSCC (6, 8). Others have found that EGFR is selectively overexpressed in HPV[−] HNSCC (9).…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of EGFR expression and signaling to HPV[+] HNSCC development and progression (compared with HPV[−] HNSCC) is not well understood. HPV oncogenes have not been shown to modulate the anti-EGFR antibody responses in HNSCC (6, 8). Others have found that EGFR is selectively overexpressed in HPV[−] HNSCC (9).…”
Section: Introductionmentioning
confidence: 99%
“…The same was found for radiotherapy-based primary treatment of oropharyngeal carcinoma with cetuximab [50]. Similarly, no differences were identified in another small cohort of HNSCC patients treated with cetuximab [47]. Other trials can also be interrogated with regard to EGFR inhibitor response and HPV status, even though these results have to be viewed with caution because of the small sample size.…”
Section: Predictive Biomarkersmentioning
confidence: 81%
“…However, neither EGFR expression nor amplification have been reported as predictive for clinical outcome after EGFR blockade (see above). Furthermore, in-vivo and in-vitro data could not show an effect of E6/E7 expression or HPV status on cetuximab efficacy [47]. Several clinical analyses have been performed to address this question.…”
Section: Predictive Biomarkersmentioning
confidence: 99%
“…Although, in laboratory settings, E5 has been suggested to enhance EGFR signaling through the inhibition of its internalization, degradation and endosome fusion (Suprynowicz et al, 2010), it is not clear if E6 and E7 also affect EGFR signaling directly. Interestingly, in a recent study, Pogorzelski et al (2014) found that HPV status does not impact cetuximab response in both in vitro and in vivo models of SCCHN (Pogorzelski et al, 2014). Similarly, in the retrospective analysis of the EXTREME trial (Vermorken et al, 2008), the authors found that the "survival benefits of chemotherapy plus cetuximab over chemotherapy alone are independent of tumor p16 and HPV status" .…”
Section: Hpv and Egfrmentioning
confidence: 91%